Two new Colombian harvestmen of the genus Quindina Roewer, 1914 (Opiliones: Nomoclastidae) - Morales, Conchita A. Pinzón; Pinto-Da-Rocha, Ricardo (Zootaxa, 2020)
Two new Colombian species of Quindina Roewer, 1915 are here described based on genital morphology and external characters. Quindina hermesi sp. nov. (type locality: Bolívar, San Jacinto) can be diagnosed externally by having a combination of colored tubercles on the ocularium, the anterior margin, areas I, II and IV of the dorsal scutum, and the free tergites; Q. discolor sp. nov. (type locality: Magdalena, Ciénaga) shows a different combination of colored tubercles on the ocularium and lateral margins. Phylogenetic analyses were performed by adding both new species to an existing matrix for Nomoclastidae. The analyses resulted in various topologies for the relationships among Nomoclastes Sørensen, 1932, Napostygnus Roewer, 1929, Kichua Pinto-da-Rocha & Bragagnolo, 2017, Callcosma Roewer, 1932 and Quindina Roewer, 1914, but all analyses recovered the monophyly of Callcosma and Quindina. This constitutes the first record of the family in northern Colombia.